2010
DOI: 10.1097/mph.0b013e3181ced36c
|View full text |Cite
|
Sign up to set email alerts
|

The Utility of Routine Surveillance Blood Cultures in Asymptomatic Hematopoietic Stem Cell Transplant Patients

Abstract: The frequency of positive surveillance BCs in asymptomatic HSCT patients at the time of hospital admission for transplant seems to be extremely low. These results, if confirmed by larger studies, show the reduced utility of obtaining surveillance BC in asymptomatic patients before administration of the conditioning regimen and the need for re-evaluation of this practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 18 publications
1
13
0
Order By: Relevance
“…59 Similarly, small case series of weekly BSI surveillance in asymptomatic children undergoing HCT demonstrated very low yield and significant cost, with no clear improvement in patient outcomes and higher rates of detection of contaminants. 60,61 Taken together, the published literature do not support the utility of surveillance blood cultures in HCT.…”
Section: Microbiological Detection Of Bloodstream Infections In Hct Pmentioning
confidence: 76%
“…59 Similarly, small case series of weekly BSI surveillance in asymptomatic children undergoing HCT demonstrated very low yield and significant cost, with no clear improvement in patient outcomes and higher rates of detection of contaminants. 60,61 Taken together, the published literature do not support the utility of surveillance blood cultures in HCT.…”
Section: Microbiological Detection Of Bloodstream Infections In Hct Pmentioning
confidence: 76%
“…A comprehensive literature search revealed only 2 published studies, both in pediatric patients, that examined the utility of obtaining SBCs in asymptomatic HCT recipients (Table 3). 25,26 These studies reported the frequency of clinically significant cultures to be between 0.5% and 7%. However, the sample size for both studies was smaller than ours, and 1 study 25 included only 1 SBC per patient, performed prior to the transplant.…”
Section: Discussionmentioning
confidence: 96%
“…The overall distribution of organisms isolated in our study was similar to the 2 articles previously cited. 25,26 Most of the positive cultures (81%) had low colony counts of organisms of questionable and low clinical significance (eg, coagulase negative staphylococci, Corynebacterium spp, other common skin inhabitants). However, the organisms isolated from SBCs of patients in group 3 included gram-positive isolates (48%) (eg, viridans group streptococci, methicillin-resistant S aureus, Enterococcus spp, including vancomycin-resistant strains); gramnegative isolates (32%) (eg, Acinetobacter spp, Klebsiella spp, Pseudomonas spp); and various other organisms (eg, Nocardia spp, Candida spp, Mycobacterium mucogenicum).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations